الأخلاق عند أبي حامد الغزالي - هاجر زغدي; كوثر نور الهدى تجاني (University of Eloued جامعة الوادي, 2025)
يستعرض هذا البحث المنظومة الأخلاقية عند الإمام الغزالي، من خلال تحليل أبعادها الفكرية والمعرفية والصوفية، وعلاقتها بالتوجهات الفلسفية والكلامية في التراث الإسلامي. ينقسم العمل إلى ثلاثة فصول رئيسية: الفصل الأول يركز على الإطار الفكري لنظرية الغزالي الأخلاقية، متتبعا جذور الأخلاق في الفكر الإسلامي قبل الغزالي، ومكانتها بين العقيدة والسلوك، مع إبراز موقف الفرق الإسلامية كالمعتزلة والأشاعرة. كما يتناول تأثر الغزالي بالمذهب الأشعري، واستيعابه للمقولات الفلسفية لدى ابن سينا والفارابي، مع نقده لها من منطلق ديني وروحي، إضافة إلى دوره في توظيف البعد الصوفي لبناء منظومة أخلاقية إصلاحية الفصل الثاني يعالج المبادئ الأخلاقية في فلسفة الغزالي، من خلال مناقشة العلاقة بين العقل والنقل في تحديد القيم، وبيان حدود العقل في تمييز الخير والشر دون هداية الشرع. كما يتضمن شرحا لنظرية الفضائل الأربع (الحكمة، الشجاعة، العفة العدالة وتفرعاتها، وموقف الغزالي من الرذائل النفسية وطرق علاجها عبر التهذيب الذاتي والتركية. الفصل الثالث يدرس نقد الغزالي للأخلاق الفلسفية، خاصة الأرسطية، ومقارنته بينها وبين التصوف الذي اعتبره طريقا للمعرفة الإلهية، كما يستعرض موقفه من الفلاسفة المسلمين ونظرته التكامل الأخلاق مع الإيمان ويختتم الفصل بتحليل طبيعة الأخلاق الغزالية في سياق التراث الإسلامي، وتأثيرها في الفكر الأخلاقي الغربي خلص البحث إلى أن الغزالي بنى نظرية أخلاقية تربط بين العقل والوحي والتجربة الروحية، وترى في تزكية النفس سبيلاً لمعرفة الله، جامعا بذلك بين الفلسفة والدين والتصوف في رؤية متكاملة. "This study explores Imam al-Ghazali's ethical system by analyzing its intellectual, cognitive, and Sufi dimensions, and its relationship to philosophical and theological trends in the Islamic heritage. The work is divided into three main chapters: The first chapter focuses on the intellectual framework of al-Ghazali's ethical theory, tracing the roots of ethics in pre-Ghazali Islamic thought. and its position between belief and behavior, highlighting the position of Islamic sects such as the Mu'tazila and the Ash'arites. It also addresses al-Ghazali's influence by the Ash'ari school of thought, his assimilation of the philosophical propositions of Ibn Sina and al-Farabi, and his criticism of them from a religious and spiritual perspective. It also discusses his role in employing the Sufi dimension to build a reformist ethical system. The second chapter addresses the ethical principles in al-Ghazali's philosophy. By discussing the relationship between reason and tradition in determining values, and clarifying the limits of reason in distinguishing good from evil without the guidance of Islamic law. It also includes an explanation of the theory of the four virtues (wisdom, courage, chastity, justice) and their branches, and Al-Ghazali's position on psychological vices and ways to treat them through self-discipline and self-restraint. The third chapter examines Al-Ghazali's critique of philosophical ethics. Especially Aristotelianism, and his comparison between it and Sufism, which he considered a path to divine knowledge. He also reviews his position on Muslim philosophers and his view of the integration of ethics with faith. The chapter concludes with an analysis of the nature of Ghazalian ethics in the context of Islamic heritage. And its impact on Western ethical thought. The research concluded that Al-Ghazali constructed an ethical theory that links reason, revelation, and spiritual experience, and that it views the purification of the soul as a path to knowing God, thus combining philosophy, religion, and Sufism in an integrated vision. "
مذكرة ماستر قسم الفلسفة تخصص فلسفة عامة
Keywords: التصوف; المعتزلة; المذهب الأشعري; الفكر الإسلامي; الأخلاق عند الغزالي; Ethics according to Al-Ghazali; Islamic thought; Ash'ari school; Mu'tazila; Sufism.